Embodied Piety: Islamic Preaching and Indigenous Identity in the Pa’bitte Passapu Ritual Dance - Ibnu Azka; Fathur Baldan Haramain (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This study examines how Islamic da’wah values interact with Indigenous identity in the Pa’bitte Passapu ritual dance of the Ammatoa people in Tanah Toa, South Sulawesi. Using ethnographic methods and symbolic-interpretive analysis over four months, data were collected from customary leaders, performers, and community members. Originating from transformed cockfighting practices and the Sawerigading–La Galigo epic, the dance conveys Islamic ethics through movements (ammiti, appasilompo manu’, sahung, abbesere, sitobo’) and kelong songs—addressing gambling and violence while promoting ta’awun, respect, and solidarity. Thus, Pa’bitte Passapu acts as “embodied piety,” harmonizing sharia and adat. It shows how the Ammatoa internalize Islamic teachings, revitalizing Indigenous tradition rather than erasing it, contributing to debates on Indigenous resilience amid religious reform and globalization in Southeast Asia.